Treatment of tardive dyskinesia caused by long-term antipsychotic use: case reports and literature review - Pabarčiūtė , I.; Karnickas , M. (Neurologijos seminarai, 2020)
Introduction. Tardive dyskinesia is a movement disorder that begins with exposure to dopamine receptor-blocking agents for at least a few months. These agents include most of antipsychotics, which are widely used to treat mental illness. This disabling condition will remain a clinical part of modern psychiatry, and the large number of publications on tardive dyskinesia that have appeared in the literature in recent years is a huge step forward in this area.Case descriptions. A 43-year-old woman with paranoid schizophrenia was hospitalized in 2018 due to constant involuntary movements of the whole body, especially expressed for ~2 years. The patient had been taking antipsychotics for about 20 years, the first dyskinetic movements were observed ~10 years ago (various jerks) and described in 2014 (champing). Tardive dyskinesia was diagnosed and the patient was treated with tetrabenazine. The patient’s condition in the hospital clearly improved, the stereotypical dystonic-hyperkinetic movements of the limbs and torso and other symptoms disappeared.Another patient, a 55-year-old woman hospitalized for involuntary movements in 2019, had been regularly taking antipsychotics for delusional disorder for ~10 years. Akathisia and hand dyskinesia appeared ~7 years ago and gradually progressed to choreoathetoid movements of the face, neck, arms, and torso. Paranoid schizophrenia and tardive dyskinesia were diagnosed during hospitalization and treatment with tetrabenazine was initiated. During treatment, the amplitude of involuntary movements partially decreased and the patient became more functional.Literature review. One of the difficulties in treating tardive dyskinesia in psychiatry is the need to continue the antipsychotics that caused the condition. In this case, the best choice would be second-generation atypical antipsychotics. The first-line treatment for tardive dyskinesia is VMAT2 inhibitors – deutetrabenazine, valbenazine; if they are not available – tetrabenazine.Conclusions. In order to provide reliable evidence-based recommendations for the treatment of tardive dyskinesia and to better understand its pathophysiology, genetic predisposition, and therapeutic agents, more studies with larger samples and more uniform conditions are needed.
Keywords: tardive dyskinesia; treatment of tardive dyskinesia